Teaching Children and Parents to Understand Dog Signaling - Meints, Kerstin; Brelsford, Victoria; De Keuster, Tiny (Frontiers in Veterinary Science, 2018)
Safe human-dog relationships require understanding of dogs' signaling. As children are at particularly high risk of dog bites, we investigated longitudinally how children from 3 to 5 years and parents perceive and interpret dogs' distress signaling gestures. All participants were then taught how to link their perception of the dog with the correct interpretation of dogs' behavioral signals and tested again. Results show a significant increase in learning for children and adults, with them showing greater understanding of dogs' signaling after intervention. Better learning effects were found with increasing age and depended on the type of distress signaling of the dogs. Effects endured over time and it can be concluded that children and adults can be taught to interpret dogs' distress signaling more correctly. Awareness and recognition of dogs' stress signaling can be seen as an important first step in understanding the dog's perspective and are vital to enable safe interactions.